Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1524838019870912
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sexual Trauma on the Sexual Health of Women Veterans: A Comprehensive Review

Abstract: Sexual trauma, particularly childhood sexual trauma, is a potent risk factor for sexual health difficulties among civilian women. Women veterans report elevated rates of sexual trauma compared to their civilian peers, including sexual trauma during military service, perhaps making women veterans even more vulnerable to sexual health difficulties. A comprehensive review of the peer-reviewed literature on the relationship between sexual trauma and sexual health in women veterans was conducted. Inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 79 publications
0
12
1
Order By: Relevance
“…Previous work has pointed toward the experience of MST as being particularly deleterious to the reproductive and perinatal health of women veterans in terms of sexual function, IPV during pregnancy, perinatal depression, and other mental health disorders during pregnancy ( Blais et al, 2018 ; Creech et al, 2021 ; Gross et al, 2020 ; Katon et al, 2018 ; Mattocks et al, 2010 ; Pulverman & Creech, 2019 ; Pulverman et al, 2019 ; Turchik et al, 2012 ). Findings from this study point toward yet another negative consequence of military sexual assault and harassment with a unique impact on women during reproductive years, and underscore the need for further study of parent-child outcomes in veteran samples to understand the intergenerational consequences of sexual trauma in military service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has pointed toward the experience of MST as being particularly deleterious to the reproductive and perinatal health of women veterans in terms of sexual function, IPV during pregnancy, perinatal depression, and other mental health disorders during pregnancy ( Blais et al, 2018 ; Creech et al, 2021 ; Gross et al, 2020 ; Katon et al, 2018 ; Mattocks et al, 2010 ; Pulverman & Creech, 2019 ; Pulverman et al, 2019 ; Turchik et al, 2012 ). Findings from this study point toward yet another negative consequence of military sexual assault and harassment with a unique impact on women during reproductive years, and underscore the need for further study of parent-child outcomes in veteran samples to understand the intergenerational consequences of sexual trauma in military service.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MST, women in the military are exposed to military medical trauma (exposure to combat injuries as a healthcare provider), and combat trauma ( Mattocks et al, 2012 ), all of which are associated with increased rates of psychopathology ( Bean-Mayberry et al, 2011 ). There is growing concern about the experience of MST as being particularly deleterious to the reproductive and perinatal health of women veterans ( Katon et al, 2018 ; Pulverman & Creech, 2019 ). For example, recent studies show that those who have experienced MST are more likely have a sexual dysfunction disorder ( Turchik et al, 2012 ) including lower sexual function and satisfaction ( Blais et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…11,12,21 Among women veterans, sexual dysfunction, including painful sex, is associated with MDD and PTSD. 18,22 Identifying and treating sexual dysfunction is important to enhancing veterans' overall health and well-being. As the entry point to the health care system, primary care is the ideal setting for identifying sexual health concerns, with primary care providers (PCPs) positioned as the first point of contact.…”
Section: Introductionmentioning
confidence: 99%
“…Female sexual dysfunction refers to an impaired ‘ability to respond sexually or to experience sexual pleasure’ (American Psychiatric Association, 2013 ) and can take different forms of impairment to the stages of sexual response, such as a decreased sexual arousal, a lack of sexual desire, inability to achieve orgasm, decreased sexual satisfaction, pain during sexual activity, or a combination of these problems (Basson, 2001 ; Hayes, Bennett, Fairley, & Dennerstein, 2006 ). Studies have shown that a history of sexual trauma is associated with impaired sexual functioning (Pulverman & Creech, 2019 ; Pulverman, Kilimnik, & Meston, 2018 ) and pelvic floor overactivity in women (Cichowski, Dunivan, Komesu, & Rogers, 2013 ; Hart et al, 2012 ; Laan & van Lunsen, 2016 ), especially when PTSD is developed (Yehuda, Lehrner, & Rosenbaum, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies investigating the relationship between trauma, sexual function and pelvic floor overactivity studied interpersonal trauma, most notably sexual trauma exposure (Hart et al, 2012 ; Pulverman & Creech, 2019 ; Pulverman et al, 2018 ; Yehuda et al, 2015 ). It is known that interpersonal trauma increases the risk for PTSD (Kessler et al, 2017 ), but it remains unclear to what extent PTSD symptoms are associated with sexual dysfunction after exposure to non-interpersonal traumatic events.…”
Section: Introductionmentioning
confidence: 99%